Women and the judiciary in the Asia-Pacific - Crouch, Melissa (Cambridge : Cambridge University Press, 2022)
Courts can play an important role in addressing issues of inequality, discrimination and gender injustice for women. The feminisation of the judiciary - both in its thin meaning of women's entrance into the profession, as well as its thicker forms of realising gender justice - is a core part of the agenda for gender equality. This volume acknowledges both the diversity of meanings of the feminisation of the judiciary, as well as the complexity of the social and cultural realisation of gender equality. Containing original empirical studies, this book demonstrates the past and present challenges women face to entering the judiciary and progressing their career, as well as when and why they advocate for women's issues while on the bench. From stories of pioneering women to sector-wide institutional studies of the gender composition of the judiciary, this book reflects on the feminisation of the judiciary in the Asia-Pacific.
The feminisation of the judiciary in the Asia-Pacific / Melissa Crouch and Natasha Naidu -- To Join the Bench and be decision-makers : women judges in Pacific Islands / Anna Dziedzic -- Women, adjudication, and judging in Sri Lanka / Dinesha Samararatne -- Women in the judiciary in Thailand / Sarah Bishop --The promise and paradox of women judges in the judiciary in Indonesia / Melissa Crouch -- Filipino women judges and their role in advancing judicial independence in the Philippines / Imelda Deinla -- One decade of female judges in the Malaysian Shari Judiciary : promises to keep and miles to go / Kerstin Steiner -- Examining women in the Nepalese Judiciary through the lens of mobility / Subas Dhakal, Justice Gauri Dhakal, and Justice Sharada Shrestha --Feminising the Indian judiciary : the gender gap and the possibilities of objectivity / Simashree Bora --Concluding remarks.
Title from publisher's bibliographic system (viewed on 22 Oct 2021).
Keywords: Women judges -- Asia; Women judges -- Pacific Area; Sex discrimination against women -- Law and legislation -- Asia; Sex discrimination against women -- Law and legislation -- Pacific Area; Women -- Legal status, laws, etc. -- Asia; Women -- Legal status, laws, etc. -- Pacific Area